Foreign Workers’ Management System - Raju, Ivan; Binti Selamat, Norhanim (Applied Information Technology And Computer Science, 2025)
The Foreign Workers’ Management System aims to improve the organization’s efficiency and compliance with managing foreign labor. The existing process depends on manual methods like spreadsheets, which creates difficulties in real-time compliance monitoring, visa processing, and decentralized document management. The objectives include developing a web-based system using an object-oriented approach and testing it through user acceptance testing. The scope of this project includes stakeholders such as the human resource department. The methodology used for implementing the Car Rental Management System is the Rapid Application Development (RAD). The abstract concludes that the system can significantly improve operational efficiency through centralized data, reducing errors, and facilitating faster processes.